The Role of the Internet in Self-Study - Gil, Alina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The concepts of teaching, learning and self-education are the most essential aspects in the processes of preparing employees for knowledge economy as well as in the processes of developing and improving skills required not only at work, but also in personal life.The Internet constitutes an essential link in educationasa basic form of teaching and a supplementary element not only in the traditional model of instruction, but also in self-education.The following article presents questions concerning self-education and the Internet as a place and technique of self-education, as well as the concept of e-learning as a modern form of distance education.